STRATEGI OPTIMALISASI KAS MENGANGGUR (IDLE CASH) DALAM PENGELOLAAN KEUANGAN DAERAH KABUPATEN ROKAN HULU - , Erwin Suhanda; , Dr. Samsubar Saleh, M.Soc.Sc., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Local financial management plays an important role in governance, community (society, people) service and sustainable development. Through the financial management of regional especially regional cash management effectively dan efficiently, is expected to take the opportunity and creating opportunities in an effort to increase revenue of local original. The purpose of this study are: 1) Calculate the potential cash idle in the cash budget in an effort to increase revenue of local original in local government Rokan Hulu regency, 2) Formulate strategy / alternative strategies to minimize idle cash in local government finance Rokan Hulu regency. The data used in this study is the primary data in the form of unstructured interviews and distributing questionnaires to the respondents selected based on purposive sampling technique-judgment. And secondary data in the form of monthly reports actual revenues and expenditures Rokan Hulu district budgets (APBD) in 2010 through the General Cash Books (BKU) regions, data deposit rate per year in 2010, the monthly revenue reports in 2010, report deposit interest income in 2010, the financial report district Rokan Hulu 2010, Rokan Hulu district laws about the 2010 budget (APBD) and RPJP 2005 to 2025. Analysis tools are used, 1) the method BIGG (Building Institutions of Good Governance)